Association of triglyceride-glucose index with bone mineral density and fracture: a systematic review - Maryam Yousefiasl; Arezou Soltanattar; Ali Ezzatollahi Tanha; Pouria Azami; Maryam Alaei; Amir Ali Alamdari; Farhad Esmailsorkh; Amirhossein Habibzadeh; Shaghayegh Khanmohammadi (Diabetology & Metabolic Syndrome, 2025)
Abstract Background and aim Studies have found inconsistent results regarding triglyceride-glucose (TyG) index and bone health. This systematic review aims to synthesize the existing evidence on the association between the (TyG) index, bone mineral density (BMD), and bone fractures. Method A comprehensive search of PubMed, Scopus, Web of Science, and Embase databases was performed for studies published up to December 26, 2024. Inclusion criteria encompassed human studies examining the TyG index in relation to BMD or fractures. The risk of bias was assessed using the Newcastle-Ottawa Scale (NOS). Data synthesis included both qualitative and descriptive statistical analyses. Results From 201 studies identified, 12 met the inclusion criteria comprising 817,242 participants. Most studies reported a significant association between TyG index and bone fractures. The studies reported inconsistent findings regarding the association between the TyG index and BMD. While some studies found no correlation between the TyG index and BMD in individuals aged ≥ 50 years, studies on the general population aged ≥ 18 years demonstrated a significant correlation between the TyG index and BMD. Variations in the age of study populations, the presence of diabetes, BMI, and adjustment factors likely contributed to these discrepancies. Further research is needed to clarify the role of the TyG index in bone health and its potential utility as a surrogate marker. Conclusion The TyG index is associated with bone fractures and can serve as a surrogate marker for osteoporosis in the general populations rather than exclusively for the elderly.